Perkembangan Pradewasa dan Kemampuan Hidup Predator Verania lineata Thurnberg (Coleoptera: Coccinellidae) pada Tanaman Padi Varietas Rojolele Transgenik - Usyati, N.; Buchori, Damayanti; Manuwoto, Syafrida; Hidayat, Purnama; Loedin, Inez H. Slamet (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
The use of transgenic varieties on the agricultural production system may provide some agronomical benefits. However, uses of transgenic variety have raised some debates about their potential negative impact on the environment, such as on the decreasing of natural enemies. To study the impact of transgenic variety to the natural enemies, study was conducted on larvae development, and the survival of predatoral insect (V. lineata) on the transgenic Rojolele rice variety. Test was conducted at the laboratory of Molecular Biology, Research Centre for Biotechnology of Indonesian Institute of Science, from January to October 2009. Completely randomized design with 8 treatments and 30 replications were employed. The treatments were transgenic Rojolele rice as follow: 4.2.3-28-15-2-7 and 4.2.4-21-8-16-4 lines contained fusion of two cry genes (cryIB-cryIAa). The 3R9-8-28-26-2 and 3R7-8-15-2-7 lines contained mpi::cryIB gene, the T9-6.11-420 line contained cryIAb gene obtained by particle bombardment, DTcry (azygous) is a segregate and does not contain cry gene (null), DTcry-13 line contained cryIAb gene by Agrobacterium, and non transgenic rice (Rojolele variety). Results showed that there were differences of larvae development and survival of insect predator V. lineata fed on the among transgenic rice lines. On transgenic line T9-6.11-420 and on DTcry-13 line the life time, developmental stages, the number eclosion of adult female, adult insect weight, and survival of the preimaginal and the adult of insect predator were consistently low. On the transgenic line 4.2.3-28-15-2-7; 3R9-8-28-26-2; and 3R7-8-15-2-7 each had no consistent effect on the larvae development and the survival of insect predator. DTcry (azygous) line had no effect on the larvae development and the survival of insect predator. Whereas transgenic line 4.2.4-21-8-16-4 had an effect on the adult weight of insect predator.